ANALISIS KELAYAKAN USAHATANI TUMPANGSARI CABAI MERAH (Capsicum annum L) DAN BAWANG MERAH (Allium cepa L) DI LAHAN PASIR KABUPATEN BANTUL - Apriansyah Apriansyah; Ignatius Suprih Sudrajat; Susi Widiatmi (JURNAL ILMIAH AGRITAS, 2019)
This study aims to determine the feasibility of intercropping farming of red chili and red onion in the sand field in Bantul Regency. The basic method used in this research is quantitative method with descriptive approach using thirty farmers for sampling randomly. They are farmers who did intercropping farming of red chilli and onion in the sand field in Srigading Village, Sanden Sub-district. The results using R / C Ratio showed that the average land area for intercropping farming of red chilli and red onion is 1230 m2, the average total cost is about Rp 11,621,226 / farming, the average revenue is Rp 46.911.033/ farming, and income earned by farmer is Rp 35.289.807 / farming. Based on the results of feasibility analysis, the R / C Ratio that was obtained is 4.04, which shows that the intercropping farming of red chilli and red onion in the sand field of Bantul Regency is feasible.